Physicochemical features assessment of acemannan-based ternary blended films for biomedical purposes - Rodrigues, Luísa Cidália Guimarães (2021)
The exploitation of natural origin macromolecules, as complex physical mixtures or drugs, increases in biomedical or tissue engineering (TE) solutions. Aloe Vera is a highly explored medicinal plant, from which the main polysaccharide is acemannan (ACE). The ACE combination with chitosan and alginate results in interactions that lead to mixed junction zones formation, predicting membrane functionality improvement. This work proposes the development and characterization of ACE-based blended films as a promising strategy to design a nature-derived bioactive platform. The results confirmed that stable complex polyelectrolyte structures were formed through different intermolecular interactions. The films present good dimensional stability, flexibility, an adequate swelling ability with mostly radial water uptake, and a sustainable ACE release to the medium. Positive biological performance of the ACE-based blended films with L929 cells also suggested that they can be applied in TE solutions, with the potential to act as bioactive topical platforms.